Mahzab Imams' Views on Breastfeeding Bank Law - Uma Khasanah Khakim; Fitri Wulandari; Zaenal Muttaqin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In Islamic jurisprudence, there is a difference of opinion among scholars regarding the permissibility of selling breast milk (ASI). The Maliki and Shafi'i schools of thought allow it, while Abu Hanifah forbids it. The scholars who permit the sale argue that breast milk is pure and lawful to consume, so there is no prohibition against selling it. They liken it to the milk of animals, which is generally permissible to sell. On the other hand, Abu Hanifah prohibits the sale of breast milk based on the argument that babies require it, and its sale could lead to exploitation. He reasons that, just as human flesh is forbidden to eat, breast milk should be treated similarly, as it is intrinsically linked to the human body. His stance is based on the analogy (qiyas) that, since human flesh is haram (forbidden) to consume, anything associated with the human body, such as breast milk, should also be considered haram to sell.